Making Contact: VAP Targeting by Intracellular Pathogens. (May 2018) - Stanhope, Rebecca; Derré, Isabelle
In naïve cells, the endoplasmic reticulum (ER) and the ER-resident V esicle-associated membrane protein- A ssociated P roteins (VAP) are common components of sites of membrane contacts that mediate the nonvesicular transfer of lipids between organelles. There is increasing recognition that the hijacking of VAP by intracellular pathogens is a novel mechanism of host–pathogen interaction. Here, we summarize our recent findings showing that the Chlamydia inclusion membrane protein IncV tethers the ER to the inclusion membrane by binding to VAP via the molecular mimicry of two eukaryotic FFAT motifs. We extend the discussion to other microorganisms that have evolved similar mechanisms.